Hacia un territorio libre de discriminación laboral por razones de orientación sexual en Villavicencio (Colombia) (2016)
The city of Villavicencio is located in the department of Meta (Colombia), it has an important number of population that belongs to LGBTI community, it is a social group that has been characterized by promoting struggles and strakes in order to obtain a recognition, specially for their human rights, one of the causes of discrimination and rejection that are reasons to become victims since the beginning of its activism until nowadays. Likewise, the human right to work has importance, so we studied discrimination in this field, given that Villavicencio is very well known by its community of macho tradition and moral habits. In this sense, the history of the community was framed under a literature review, and to conclude the research field, there were studies that aimed to know the perception and experiences of those affected in the workplace. In this way, it was possible to establish that at the present the persons belonging to this group in Villavicencio suffer the phenomenon of the segregation, in reason of their sexual choice, the most affected are the genre of transgender, the job that they develop influences strongly in discriminatory acts. Nevertheless, in the job sector these practices are not so visible because of the preference of the members of the community to hide their sexual orientation to obtain access for a job vacancy, or to get a job.